Islamic Views on Concubinage: Exploring the Rights and Status of Female Slaves (Al-Qamar, 2020)
One of the objections raised against Islam is the abuse and oppression of women. A recurrent objection in this regard is that Islam treats female slaves inhumanely. Addressing this objection, the present paper explores the rights of female slaves in Islam. It finds that female slaves have been enjoying privileged protection in the Muslim society that is uncommon to any other system of slavery in history. Concubines have been exploited through corrupt systems of slavery all over the world. The vice of such exploitation eventually entered the Muslim society as well. The farce face of the later Muslim society cannot be taken as a true picture of Islam, because many of its exploitative operations did not match the teachings contained in original Islamic sources.
Keywords: Islam; objections; women; concubines; rights